2019
DOI: 10.1016/j.joca.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

T2* and quantitative susceptibility mapping in an equine model of post-traumatic osteoarthritis: assessment of mechanical and structural properties of articular cartilage

Abstract: Objective: To investigate the potential of quantitative susceptibility mapping (QSM) and T2* relaxation time mapping to determine mechanical and structural properties of articular cartilage via univariate and multivariate analysis. Methods: Samples were obtained from a cartilage repair study, in which surgically induced full-thickness chondral defects in the stifle joints of seven Shetland ponies caused post-traumatic osteoarthritis (14 samples). Control samples were collected from non-operated joints of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Prior to MRI, all samples (14 experimental and six control) underwent biomechanical indentation testing of cartilage surrounding the repaired lesions, as described before. 21,22 In short, the samples were submerged in phosphate-buffered saline (PBS) and glued on a custom-made sample holder. First, a plane-ended indenter (d = 0.53 mm) was driven in contact with the sample.…”
Section: Biomechanical Measurementsmentioning
confidence: 99%
“…Prior to MRI, all samples (14 experimental and six control) underwent biomechanical indentation testing of cartilage surrounding the repaired lesions, as described before. 21,22 In short, the samples were submerged in phosphate-buffered saline (PBS) and glued on a custom-made sample holder. First, a plane-ended indenter (d = 0.53 mm) was driven in contact with the sample.…”
Section: Biomechanical Measurementsmentioning
confidence: 99%
“…If surgical intervention such as micro-fracture [ 3 ] or cartilage replacement [ 4 , 5 , 6 ] to degenerated or damaged cartilage is necessary, there are the following two potential approaches to know the mechanical property of articular cartridge. In pre-operative and post-operative phases, quantitative magnetic resonance (MR) images is one approach (noninvasive approach) [ 7 , 8 ]. If the quantitative MR images can detect not only lesion area, and they can provide mechanical property of the cartilage tissue, we can match the mechanical property of tissue or material for the cartilage replacement with the mechanical property of marginal area around the lesion.…”
Section: Introductionmentioning
confidence: 99%
“…Also, relatively new quantitative MR images such as ultrashort echo time (UTE) magnetization transfer (UTE-MT) and UTE-T2* mapping have been reported for diagnosis of early cartilage degeneration [ 12 , 13 , 14 , 15 , 16 ]. However, only a few studies reported on the correlation between quantitative MR images and classical mechanical properties of the articular cartilage [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation could be that the superficial zones are damaged or partly disappeared, such that the average T2* values within the VOI mostly reflect the middle and deep zone of the cartilage. Several studies have shown a tendency to a decrease in T2* relaxation times from superficial to the deep zone 4,19. Hesper et al7 found that T2* relaxation times were lower in damaged cartilage, as evaluated by arthroscopy.…”
mentioning
confidence: 99%